Synthesis of green zero-valent iron using polyphenols from dried green tea extract - Borja, Josephine Q. (Animo Repository, 2015)
Green zero-valent iron (ZVI) was synthesised using polyphenols from green tea extract as reducing agent and ferric chloride (FeCl3) as iron precursor. Polyphenols were extracted through microwave-assisted extraction from dried green tea leaves with varying green tea-to-solvent ratio (1:18-1:22 g/mL). During ZVI synthesis various green tea extract flow rate (8-17 mL/min) and ferric chloride-to-green tea extract ratio (1:1-1:3 mL/mL) were investigated. The most favourable conditions for the synthesis of green ZVI was determined based on the yield, rate of oxidation and surface area of the metal product. The conditions which gave the highest yield of 86.48% were the following: green tea-to-solvent ratio of 1:20, green tea extract flow rate of 8mL/min and a FeCl3-to-green tea extract ratio of 1:2. On the other hand, the conditions which gave the smallest particle size (8.82 nm) were the following: green tea-to-solvent ratio of 1:20, a green tea extract flow rate of 17 mL/min and a FeCl3-to-green tea extract ratio of 1:3. It was determined that the green tea extract flow rate was the only factor that significantly affected both the particle size and the yield. The factors tested did not have significant effect on the rate of oxidation of the metal product. © School of Engineering, Taylor’s University.